Emotional Diplomacy : Official Emotion on the International Stage - Hall, Todd H., 1976- (Book collections on Project MUSE., 2015)
This book explores the politics of officially expressed emotion on the international stage, looking at the ways in which state actors strategically deploy emotional behavior to shape the perceptions of others. Examining diverse instances of emotional behavior, the book reveals that official emotional displays are not simply cheap talk but rather play an important role in the strategies and interactions of state actors.